Learning Motivation of Students Whose Learning Processes Are Combined and Separated Between Boys and Girls in One Class - Radiyatan, Mutiah; Mudjiran, Mudjiran (Universitas Negeri Padang, 2022)
This research is motivated by the presence of students whose learning processes are combined and separated between men and women in one class where each type of class has a different type of learning motivation. This is influenced by intrinsic factors and extrinsic factors in each student. The purpose of this study is to determine the percentage of students' learning motivation. The type of research used is quantitative with descriptive methods. The research sample was class XII students at MAN 2 Padang City, totaling 188 people who were selected using a proportional random sampling technique. Data is processed using interval and percentage formulas. The results of the study revealed that students whose learning processes were combined by boys and girls were in the high category with a percentage of 59.81%, classes where there were only boys were in the high category with a percentage of 46.34%, and classes where there were only boys there are women who are in the high category of 57.50%.